Wet Mount Microscopy A Better Diagnostic Tool for Bacterial Vaginosis Screening than Gram Staining (Medical Forum Monthly, 2024)
Objective: To compare Wet smear and Gram staining for Clue cells in screening Bacterial Vaginosis (BV) in a clinical setting where laboratory facilities are not readily available.Study Design: Cross-SectionalPlace and Duration of Study: This study was conducted in the Department of Microbiology, Basic Medical Sciences Institute Jinnah Postgraduate Medical Center Karachi. High vaginal swabs (HVS) were collected from Gyne & Obstetric Department of Jinnah Postgraduate Medical Centre, Karachi, from Jan 2005 to Feb 2007.Materials and Methods: One hundred and fifty high vaginal swabs (HVS) were collected from married females with or without complain of vaginal discharge. BV was diagnosed on the basis of clinical Amsel’s criteria BV was diagnosed. Subsequently, clinical diagnosis was compared with laboratory based diagnosis for each woman. Two methods used were Wet Mount and Gram Staining. Results: Out of total 150 cases, 100 females were complaining of vaginal discharge and after clinical assessment by Amsel,s criteria 34 (34%) were diagnosed as cases of BV. Fifty females as (as controls) were those who were not complaining of any discharge. But among this group 8 (16%) were discovered to be suffering from BV. With the help of wet mount, the clue cells were visualized in 61 (40.7%) cases, while by Gram staining 54 cases (36.0%) were seen. Conclusion: BV screening is important as it affects both groups of females with or without complains of discharge. For easier recognition of clue cells, which are an excellent predictor of BV, wet mount is better as compared to Grams staining method.